The Effect of Stem-Based Learning Module on Students Learning Outcomes and Motivation in General Chemistry Courses - Pane, Eva Pratiwi; Manurung, Hisar Marulitua; Simangunsong, Anita Debora; Mobo, Froilan D.; Siahaan, Theresia Monika; Manurung, Suprapto (Universitas Muhammadiyah Mataram, 2022)
This study aims to determine the effect of STEM-based learning modules on learning outcomes and student motivation in general chemistry courses. This research is a quantitative research. This research was conducted at the Faculty of Teacher Training and Education, University of HKBP Nommensen Pematangsiantar in September 2021-January 2022. The type of research used was a quasi-experimental design using a Non-Equivalent Control Group pretest-posttest design. Data collection methods used were multiple choice tests to measure learning outcomes and questionnaires to analyze learning motivation. The results showed that the use of STEM-based modules had an effect on student learning outcomes and motivation in general chemistry courses. The increase in learning outcomes in the experimental class can be seen from the large percentage of students who get high N-Gain scores in the experimental class, which is 67.8% compared to the percentage of students who get high N-gain scores in the control class. class that reaches 20%. The use of STEM-based learning modules can increase students' learning motivation, namely learning motivation as much as 76% in the very high category, 9% in the high category, and 15% in the medium category, and none of the students have learning motivation in the low and very high low categories. . The conclusion of this study is that there is a very significant influence through STEM-based learning modules on student learning outcomes and motivation in general chemistry courses.